Steuergeldwäscherei in Bezug auf direkte Steuern Ein Beitrag zur Auslegung von Art. 305bis Ziff. 1 und Ziff. 1bis StGB - Bourquin, Gabriel (Carl Grossmann Verlag, 2017)
The present analysis focuses on the interpretation of art. 305bis of the Swiss Criminal Code. The author, Gabriel Bourquin, treats the problem of tax crimes as predicate offenses to money laundering. Where necessary, in particular in relation to the punishment of money laundering by omission, the analysis will deal with the special duties of due diligence (art. 6) and the duty to report (art. 9) of the Anti-Money Laundering Act.